'One man's junk culture..': A state-of-the-art review on the problem of mass culture in Argentine cultural studies - Labra, Diego (2020)
Could you truly understand contemporary Argentine culture without considering the local appropriation of The Simpsons? In this article, we argue that mass culture has been a blind spot of Argentine social sciences and humanities because of the particular development of local cultural studies. In order to articulate a critique and build upon it, we will review relevant literature, identify promising current research, and offer an outline on how to rethink the problem of production, circulation and consumption of culture in 21st-century Argentina and beyond.